La discriminación como factor influyente en el desempeño laboral de las y los oficiales con discapacidad y enfermedades catastróficas en la Sub Zona 11 de la Policía Nacional - Loja en el periodo 2016-2017 y la intervención del Trabajador/a Social - PAREDES DUARTE, ANDREA ELIZABETH (2018)
For the realization of this work of research, has been located as a case study to the institution of the police national Loja - Sub area 11, through a preliminary survey which found that discriminatory conduct influence negatively in the and officials with catastrophic diseases and disability affecting them moral staff and physically seeing this reflected in low production levels. This work had as general objective to determine the existence and form that discriminatory conduct affect job performance of and officials with disabilities or catastrophic illnesses, same that was achieved through the goals specific where it was determined the causes and consequences and was theoretically based categories related to: disability, catastrophic diseases, discrimination, laws and rights of persons with disabilities and catastrophic diseases and the the Social worker/a intervention. The scientific method, was used to make the research process through the application of auxiliary methods as: deductive, inductive method, analytical and synthetic what helped check its feasibility and scientific validity. Applied survey 45 officers of the institution (15 officers with catastrophic diseases and disability) and 30 officers of the same work environment and an interview structured at 3 representative of the institution figures (a Colonel administrative and) Operating, a psychologist and a Social worker), in order to assess the knowledge of the members make a contrast between the responses obtained, and thus to comply with the objectives of this research. In this examination the existence of discriminatory, same behaviors that influence the work performance of the officers with catastrophic diseases and disability, you can clearly see what led to the formulation of a proposal for intervention Social for timely mediation.